Pengaruh Pemberian Urea Molease Mineral Blok terhadap Kadar Mineral Serum Sapi yang Memperlihatkan Gejala Defisiensi Mineral - Mira Delima (Agricultural Faculty, 2008)
The effect of urea molasses mineral block administration on mineral deficiency content of cattles serum mineralABSTRACT. A study has been done to find the influence of urea molasses mineral block (UMB) on cattle. The cattle those used in the research were public cattle. The cattle applied were 12 females at the age of 12-18 months which showed mineral deficiency symptoms, and the laboratory analysis result showed that they were lack to one or more mineral element of Ca, Cu, Mg, or P in their serum. UMB was provided to the cattle in the cage all day long (ad libitum) during 3 months. Keeping of the cattle was done in the following pattern: in the evening (18.00p.m - 11.00a.m) cattle were penned, and between 11.00a.m - 18.00p.m were discharged freely in rice field, grassland, or garden, therefore they could foraging around. Blood sample was taken immediately before research was started, which was counted as day 0. It followed with day 42nd, and day 84th. The result study indicates that giving of UMB have no effect on mineral level of Ca, Cu, and Mg in the serum. However, it causes increasing the P level.